Effects of cold plasma treatment on the biological performances of decellularized bovine pericardium extracellular matrix-based films for biomedical applications - Maria Elena Lombardo; Valentina Mariscotti; Pascale Chevallier; Francesco Copes; Francesca Boccafoschi; Andranik Sarkissian; Diego Mantovani (Exploration of BioMat-X)
Aim: Since decades, decellularized extracellular matrix (dECM)-derived materials have received worldwide attention as promising biomaterials for tissue engineering and biomedical applications. Soluble dECM is a versatile raw material that can be easily engineered into the desired shapes and structures. However, there are still some limitations restricting its use, including low hydrophilicity and smooth surfaces, which negatively influence cell adhesion/spreading. The objective of the present study was to investigate surface modification by nitrogen/hydrogen (N2/H2) low-pressure cold plasma treatment as a potential technique to improve the biological response of bovine pericardium dECM films. Methods: Bovine pericardium dECM was enzymatically digested and lyophilized prior to the preparation of thin films via solvent-casting method. Changes in surface properties after plasma treatment were investigated using water contact angle (WCA) and X-ray photoelectron spectroscopy (XPS) measurements. Immunofluorescence staining and resazurin assay for human dermal fibroblasts (HDFs) cultured on the dECM films were used to assess the bioactivity of dECM films. Finally, the hemocompatibility of the films was investigated via clotting time and hemolysis assay. Results: WCA and XPS results revealed that oxygen (O)- and N-containing functional groups were incorporated onto the film surface and an increase in hydrophilicity was observed after plasma treatment. In vitro experiments showed that cell adhesion in plasma-treated dECM films is much faster if compared to the untreated controls. Moreover, the fibroblast proliferation increased after plasma surface modifications. Finally, the hemocompatibility analysis results indicated a delayed blood clotting and no hemolytic effects for all the tested samples. Conclusions: These findings confirmed the potential of dECM as raw material for biocompatible thin films fabrication. Additionally, plasma surface treatment emerged as an eco-friendly and cost-effective strategy to enhance in vitro cell attachment and proliferation on dECM films, expanding their applications in biomedicine.